Amendments to the treatment regulations at a psychiatric hospital as the element shaping culture in terms of human rights - Kmieciak, Błażej (Polish Journal of Public Health, 2018)
A psychiatric hospital is a special place. People undergoing treatment are in a unique situation. Mental illness remains a mystery for scientists because we do not know what factors influence its appearance. There were also no drugs that would completely cure the patient, as you never know whether the medicine will affect a particular person. Mental illnesses evoke anxiety and fear of the community. Some patients take disturbing or dangerous actions. Their behaviors are referred to as specific and different ones. A similar situation is caused by the appearance of psychotic symptoms. One should pay attention to delusions and hallucinations here. These symptoms cause the patient’s situation to deteriorate. Ultimately, they can cause dangerous behavior.It happens that a relative of a patient, who is in such condition, must take action without his/her consent. A similar issue has been analyzed in Poland for almost thirty years. Individual regulations, in exceptional cases, allow for undertaking coercive actions: treating the patient without consent, applying direct coercion. These interventions are controlled. Polish psychiatric legislation is constantly changing (new control institutions are introduced, the role of the family court is increased). This article presents the latest amendments. They are based on the principle of respect for human rights and freedoms.